Bank lines of credit as contingent liquidity: A study of covenant violations and their implications - Viral Acharya; Heitor Almeida; Filippo Ippolito; Ander Perez (European Central Bank (ECB), 2014)
We study how the consequences of violations of covenants associated with bank lines of credit to firms vary with the financial health of lenders. Following a violation banks restrict usage of lines of credit by raising spreads, shortening maturities, tightening covenants, or cancelling the line or reducing its size. Even though the frequency of covenant violations is fairly stable during the period 2002-2011, the reaction of banks to violations became significantly more restrictive during the recent crisis. Banks in worse financial health are more likely to restrict access to credit lines following a violation, and violations driven by lender health have capital structure and real implications for firms. This behavior is at the heart of a new bank liquidity channel. This channel complements the traditional bank lending channel, which focuses on small financially constrained firms, because credit lines are commonly used by large, high credit quality firms to provide insurance against loss of access to external finance.
Keywords: G21; G31; G32; E22; E5; 330; bank financial health; covenant violations; firm financial constraints; lines of credit